Price Spread, Marketing Efficiency and Constraints in Marketing of Chayote (Sechium edule) in Mizoram - sangpuii, Lalrin; Malhotra, R. (Indian Journal of Hill Farming, 2019)
The present study was conducted to study price spread, marketing efficiency and constraints in marketing of chayote in Mizoram state. The data for the study was collected during the period 2014-15 and was analysed using statistical tools such as percentages, ratios, means and frequency distribution. The study identified three marketing channels in the study area i.e, Channel I (Producer – Commission agent (Association marketing societies) - Retailer – Consumer), Channel II (Producer - Wholesaler – Retailer – Consumer) and Channel III (Producer - Consumer), of which Channel I was the most important channel. Among the three marketing channels identified in the study area, the producers received highest share under Channel III followed by Channel I and the consumer’s price was highest under Channel I. Marketing efficiency of chayote was highest in channel – III followed by channel-I and channel- II. In order to improve the marketing efficiency and producer share in consumer’s price, it is necessary to reduce the number of intermediaries in marketing supply chain as well as to reduce marketing cost and marketing losses. Among the various marketing problems stated by chayote growers, price fluctuation was the most important problems. There is a need to establish regulated market in the state and improve the marketing system through market intelligence, market research and development and market extension in the area.